The Mediation Role of Job Satisfaction in Improving Nurse Performance of General Hospital’s Type A at Central Java - Desti Ranihusna; Suharnomo Suharnomo; Fadila Arifinandini (Management Analysis Journal, 2023)
This study aims to determine the effect of compensation and organizational culture on job satisfaction and performance, as well as the effect on performance through job satisfaction as hospital nurse. The population in this study was Hospital Inpatiction Room Nurse. The sampling technique employed purposive sampling technique with a total sample of 179 nurses. The data processing technique employed the Partial Least Square (PLS) based method to develop the reliability of construct variables in model analysis. The results of this study indicate that compensation has a significant effect on performance, but organizational culture has no significant effect on performance. Job satisfaction mediates the effect of compensation on performance and the influence of organizational culture on performance. Suggestions for further researchers to use job satisfaction as a mediating variable in improving performance.